Overcoming the Drawbacks of Sulpiride by Means of New Crystal Forms - Rebecca Birolo; Federica Bravetti; Simone Bordignon; Ilenia D'Abbrunzo; Paolo P. Mazzeo; Beatrice Perissutti; Alessia Bacchi; Michele R. Chierotti; Roberto Gobetto (MDPI AG, 2022)
This study aims at developing new multicomponent crystal forms of sulpiride, an antipsychotic drug. The main goal was to improve its solubility since it belongs to class IV of the BCS. Nine new adducts were obtained by combining the active pharmaceutical ingredient with acid coformers: a salt cocrystal and eight molecular salts. In addition, three novel co-drugs, of which two are molecular salts and one is a cocrystal, were also achieved. All samples were characterized in the solid state by complementary techniques (i.e., infrared spectroscopy, powder X-ray diffraction and solid-state NMR). For systems for which it was possible to obtain good-quality single crystals, the structure was solved by single crystal X-ray diffraction (SCXRD). SCXRD combined with solid-state NMR were used to evaluate the ionic or neutral character of the adducts. In vitro dissolution tests of the new crystal forms were performed and all the adducts display remarkable dissolution properties with respect to pure sulpiride.